2016
DOI: 10.1016/j.cell.2016.06.043
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-Induced Antibodies that Neutralize Group 1 and Group 2 Influenza A Viruses

Abstract: Antibodies capable of neutralizing divergent influenza A viruses could form the basis of a universal vaccine. Here, from subjects enrolled in an H5N1 DNA/MIV-prime-boost influenza vaccine trial, we sorted hemagglutinin-cross reactive memory-B cells and identified three antibody classes, each capable of neutralizing diverse subtypes of group 1 and 2-influenza A viruses. Co-crystal structures with hemagglutinin revealed that each class utilized characteristic germline genes and convergent sequence motifs to reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
414
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(436 citation statements)
references
References 39 publications
19
414
3
Order By: Relevance
“…However, the V H 3–30 family uses an extended CDR H3 to occupy the same pockets as the IFY motif of the V H 1–69 antibodies. More recently, a number of vaccine-induced antibodies that arise from other heavy chain germline families have been shown to target this same site 60 . Thus, these finding have led to the concept of a headless HA as an immunogen that would focus the immune response on the HA stem and away from the more immunogenic head region 61 .…”
Section: Design Of a More Universal Vaccinementioning
confidence: 99%
“…However, the V H 3–30 family uses an extended CDR H3 to occupy the same pockets as the IFY motif of the V H 1–69 antibodies. More recently, a number of vaccine-induced antibodies that arise from other heavy chain germline families have been shown to target this same site 60 . Thus, these finding have led to the concept of a headless HA as an immunogen that would focus the immune response on the HA stem and away from the more immunogenic head region 61 .…”
Section: Design Of a More Universal Vaccinementioning
confidence: 99%
“…In a recent study, HA cross-reactive memory B cells were isolated from subjects immunized with an H5N1 DNA/inactivated virus prime-boost influenza vaccine[120]. Three antibody classes were recognized, and each of them were able to neutralize distinct subtypes of group 1 and group 2 influenza A viruses.…”
Section: Passive Immunization With Monoclonal Antibodies Inducingmentioning
confidence: 99%
“…In non‐human primates, for instance, we showed that while the choice of adjuvant could impact the ELISA titer of the vaccine response, it did not increase the levels of somatic hypermutation (SHM) in vaccine‐elicited lineages, which remained far below those seen in models of infection 23. Antibodyomics2 was used to monitor the elicitation and expansion of influenza broadly neutralizing antibodies in response to immunization with an H5N1 strain [16 and manuscript in preparation]. We have also used longitudinal information to analyze the rate of antibody evolution.…”
Section: Antibodyomics2mentioning
confidence: 99%
“…More recently, mouse models incorporating knock‐in germline genes has demonstrated the priming of multidonor VRC01 class antibodies in response to germline‐targeting immunogens 58, 60, 67. We have also applied Antibodyomics5 to the quantification of multidonor class antibodies that neutralize both group 1 and group 2 influenza A viruses 16. We delineated antibody sequence signatures and quantified antibodies that satisfy these sequence signatures in NGS datasets from multiple donors with different vaccination histories 52, 68.…”
Section: Antibodyomics5mentioning
confidence: 99%
See 1 more Smart Citation